Hippocampal serotonin depletion unmasks differences in the hyperlocomotor effects of phencyclidine and MK-801: quantitative versus qualitative analyses - Adams, Wendy K.; Halberstadt, Adam; Van Den Buuse, Maarten (Frontiers in Pharmacology, 2013)
Antagonism of N-methyl-D-aspartate (NMDA) receptors by phencyclidine is thought to underlie its ability to induce a schizophrenia-like syndrome in humans, yet evidence indicates it has a broader pharmacological profile. Our previous lesion studies highlighted a role for serotonergic projections from the median, but not dorsal, raphe nucleus in mediating the hyperlocomotor effects of phencyclidine, without changing the action of the more selective NMDA receptor antagonist, MK-801. Here we compared locomotor responses to phencyclidine and MK 801 in rats that were administered 5,7 dihydroxytryptamine (5,7-DHT) into either the dorsal or ventral hippocampus, which are preferentially innervated by median and dorsal raphe, respectively. Dorsal hippocampus lesions potentiated phencyclidine-induced hyperlocomotion (0.5, 2.5 mg/kg), but not the effect of MK-801 (0.1 mg/kg). Ventral hippocampus lesions did not alter the hyperlocomotion elicited by either compound. Given that phencyclidine and MK-801 may induce different spatiotemporal patterns of locomotor behavior, together with the known role of the dorsal hippocampus in spatial processing, we also assessed whether the 5,7-DHT-lesions caused any qualitative differences in locomotor responses. Treatment with phencyclidine or MK-801 increased the smoothness of the path travelled (reduced spatial d) and decreased the predictability of locomotor patterns within the chambers (increased entropy). 5,7-DHT-lesions of the dorsal hippocampus did not alter the effects of phencyclidine on spatial d or entropy—despite potentiating total distance moved—but caused a slight reduction in levels of MK-801-induced entropy. Taken together, serotonergic lesions targeting the dorsal hippocampus unmask a functional differentiation of the hyperlocomotor effects of phencyclidine and MK 801. These findings have implications for studies utilising NMDA receptor antagonists in modeling glutamatergic dysfunction in schizophrenia.